Enhancement of High School Students’ Scientific Literacy Using Local-Socioscientific Issues in OE3C Instructional Strategies - Saija, M.; Rahayu, S.; Fajaroh, F.; Sumari, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Guided inquiry learning has improved scientific literacy skills in various studies. This fact, however, contradicts new findings from the 2015 PISA survey. The research aims to assess inquiry-based OE3C learning methodologies that incorporate local socioscientific issues (SSI) to improve students’ scientific literacy. The research method used quantitative and qualitative methods to evaluate the planned strategy for teaching thermochemistry and rate reactions. The local SSI-based OE3C was used in a sixteen 90-minute lesson with 72 eleventh-grade students (experimental group) at an Indonesian public high school. A control group of 68 students from the same school was taught using guided inquiry learning. The experimental group received a 17-item questionnaire on students’ opinions of the instructional process using the OE3C based on local SSI and a 24-item scientific literacy test (Cronbach alpha = 0.717) from pretest and posttest. The control group also received the scientific literacy tests from pretest and posttest. The finding shows that OE3C learning based on SSI effectively enhances students’ scientific literacy skills. These findings are consistent with the results of the student perception questionnaire, which are supported by semi-structured interview findings 7.78% of students are highly pleased to learn using local SSI-based OE3C learning, and 95.83% of students think that learning to use local SSI-based OE3C learning steps helps them gain a better knowledge of the material. The findings of this study suggest that local SSI should be integrated into chemistry classes to help students build scientific literacy skills.